STUDY ON THE ATTRACTIVENESS OF THE PHYSICAL EDUCATION CLASS FOR MIDDLE SCHOOL STUDENTS - LUPU Gabriel Stănică (Editura Universitatii Transilvania din Brasov, 2020)
The physical education teacher plays a complex role in the professional activity, he/she is a guide of the sports movement, he/she plans, cooperates and stimulates the students. Knowledge of motivational factors in active and conscious participation in the physical education class of students involves the choice of modern means and methods in the application of physical exercise. Hypothesis: careful knowledge of students' preferences for various physical activities and adjustment of the means of action to these preferences lead to an increase in the attractiveness of the physical education class. The study was performed on 89 middle school students in Bacau. Two quizzes were applied, one aimed at the current assessment of the attractiveness of the physical education class and one aimed at students' expectations of the education physical class and teacher. The results of the study showed that there is a strong correlation between the degree of involvement in the physical education class and the students' preferences for exercising